Exploration of ammonium sulfate as a by-product using loaded clinoptilolite from swine permeate at high pHs with sodium sulfate - Herrera, Jaime (Kansas State University, 2024)
Population is expected to increase both globally and domestically, increasing the demand for food, water, energy, and resources. To meet this food demand and to keep costs relatively low to the consumer, industrial farming methods have increased in the past decades in the form of concentrated animal feeding operations (CAFOs). These concentrated/confined animal feeding operations (CAFOs) are characterized by the amount, type of livestock and by having minimal to insufficient surrounding agricultural land where the manure from these operations can be applied. Conventional storage practices and overapplication pose an environmental threat as surface runoff, leaching, and/or devastating breach due to the excessive amount of solids, nutrients, biological oxygen demand (BOD), and bacteria that threaten surface water, groundwater, air quality, human health, and wildlife. An emergent technology that can take advantage of the concentrated amounts of manure while removing solids, BOD, recycle water, provide the potential to extract nutrients and generate energy in the form of biogas, is an anaerobic membrane bioreactor (AnMBR). This type of technology has been commercialized in the food industry but is relatively novel in the application of manure and municipal treatment. Ongoing research at Kansas State University focuses on the treatment of swine manure from CAFOs. The goal of the AnMBR research team is to collect data, monitor parameters through various stages of the process, overcome membrane fouling, observe system performance, maintain desirable conditions for biogas producing organisms, recover nutrients from permeate, and determine final quality effluent after further polishing from artificial wetlands. This study focused on the nutrient recovery aspect of the AnMBR process, specifically the recovery of ammonia and ammonium ion from the permeate using clinoptilolite (CLI) zeolite and the regeneration of the CLI to create a liquid fertilizer product in the form of ammonium sulfate. Numerous studies have shown the kinetics and affinity of CLI towards cations. Varying studies have confirmed the affinity for cation exchange to generally follow a Cs⁺>Rb⁺>K⁺>NH₄⁺>Ba²⁺>Sr²⁺>Na⁺≈Ca²⁺>Fe³⁺>Al³⁺>Mg²⁺≈Li⁺ and K⁺>NH₄⁺>Na⁺>Ca²⁺>Mg² sequence, for competing cations in reagent solutions and sewage municipal wastewater, respectively. Previous studies have also shown successful regeneration of CLI above 69% with a brine solution. Lastly, a recent study discovered high efficiency regeneration of CLI, above 90%, using sodium sulfate solution and sodium hydroxide at a pH that ranged from 12.6-12.9 that created an ammonium sulfate product. Influenced by the knowledge of previous studies and behavior of CLI, the experiments conducted in this study sought to create a non-saline regenerant with an ammonium sulfate by-product; at a relatively lower pH with the use of sulfuric acid, the use of permeate with its varying cations composition to displace ammonia/ammonium ions, the use of 1M sodium sulfate solution as a stand-alone regenerant, and 1 M sodium sulfate with the combination of sodium hydroxide at pHs of 8, 9, 10 and 12. The experiments demonstrated that the use 1M sodium sulfate and minimal amounts of sodium hydroxide as a regenerant at pH 9 yielded the highest ammonia/ammonium desorption rate from clinoptilolite loaded with ammonia-N derived from swine AnMBR permeate. The other conditions revealed variable levels of ammonia-N release, but below the pH 9 condition described above. The methodology, results, and discussion of these experiments will be further explained in this report.
Keywords: Swine permeate; AnMBR; Nutrient recovery; Clinoptilolite regeneration; Ammonia adsorption; Sodium sulfate; Concentrated animal feeding operations